The Translation Shifts Of Andrea Hirata’s Laskar Pelangi Into The Rainbow Troops By Angie Kilbane - Maitri Ramadhani; Yusrah (LPPM STKIP AL MAKSUM, 2023)
This paper investigates the translation shifts in Andrea Hirata’s Laskar Pelangi Into The Rainbow Troops By Angie Kilbane as the consequence of interference of the mother language in translating SL into TL. It focuses on the shifts that occur in Source Text and Target Text in terms of Catford’s category shifts. Descriptive Translation Studies (DTS) is used in analyzing the texts. The texts are separated into clauses and analyzed based on Catford’s category shifts. It is argued that the interference of the First Language affects in translating ST into TT. It was found that: a) unit shift, class shift, and the very common one- the structural shift occurred in translating the text, b) expanding text occurs in which the TT has explained more detail than the ST, c) It was also found that there are two kinds of interference between ST and TT i.e. Syntactic/Grammatical interference and Lexical/Semantic interference as shifts are the reflection of the translator’s first language interference)